Impact of the detonation gas spraying mode on the phase composition and adhesional strength of Ti-Si-C coatings - Rakhadilov, B.K; Buitkenov, D.B.; Wieleba, W.; Kylyshkanov, M.K.; Yerbolatuly, D. (KU publ., 2020)
The work considers the research results of the phase composition and strength characteristics of detonation coatings based on Ti-C-Si, which obtained for different values of the volume of filling the detonation barrel with an explosive acetylene-oxygen mixture. It was determined that with an increase in the volume of filling the detonation barrel with an explosive mixture up to 70% of the coating are mainly consist of TiC phases. Since Ti3SiC2 powder heated to high temperatures partially decomposes into TiC as a result of high-speed shock interaction. The results of X-ray phase analysis showed that a low degree of decomposition of Ti3SiC2can be achieved under filling the barrel with an explosive mixture of 50% and 60% and the coatings mainly consist of Ti3SiC2 phases with a low TiC content. This is due to the fact that the heating temperature of the sprayed powder increases with increasing in the degree of filling of the detonation barrel with an explosive acetylene-oxygen mixture. It was determined that an increase in the volume content of the TiC phase in the coating composition leads to a decrease in the hardness of the Ti-C-Si coating. The results of the research of the adhesive strength of coatings showed that the effect of the volume of filling the detonation barrel with an explosive mixture on the adhesive strength is negligible. Moreover, all coatings based on Ti-C-Si, obtained by the detonation method, showed good adhesive strength.
Детонациялық газды тозаңдату режимінің Ti-Si-C жабындарының фазалық құрамына және адгезиялық беріктігіне әсері
Влияние режима детонационного газового напыления на фазовый состав и адгезионную прочность покрытий Ti-Si-C
Keywords: detonation spraying; titanium carbosilicide; steel; phase; adhesion